SRPES and STM data for the model bimetallic Pd-In/HOPG catalysts: Effects of mild post-synthesis oxidative treatments - M.A. Panafidin (Elsevier, 2021)
Post-synthesis treatment of bimetallic catalysts in different gas phases resulting in the adsorption-induced segregation is among promising approaches to enhance their activity not compromising selectivity towards a number of low-temperature reactions. Our recently published paper (M.A. Panafidin, A.V. Bukhtiyarov, I.P. Prosvirin, I.A. Chetyrin, A.Yu. Klyushin, A. Knop-Gericke, N.S. Smirnova, P.V. Markov, I.S. Mashkovsky, Y.V. Zubavichus, A.Yu. Stakheev, V.I. Bukhtiyarov, A mild post-synthesis oxidative treatment of Pd-In/HOPG bimetallic catalysts as a tool of their surface structure fine tuning. Appl. Surf. Sci.) reports on Pd-In intermetallic formation regularities and their evolution after storage in air as well as during treatment in oxygen at submillibar pressures. The current paper gives an extended representation of experimental ex situ/in situ synchrotron-based photoelectron spectroscopy (SRPES) and scanning tunnelling microscopy (STM) data used to derive scientific conclusions in the paper quoted above.